Impact of green transformational leadership on job performance: The mediating role of psychological contract fulfillment - Razia Bano; Ifzal Ahmad; Mehfoozullah Ullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Green transformational leadership is a style that has the potential to not only shape individual behaviors towards more environmentally friendly behaviors, but it has also the potential to impact the employees' other non-green behaviors. This paper aims to investigate the impact of green transformational leadership style on employees' non-green behavior i.e. job performance. The study further explored the mediating role of psychological contract fulfillment between the green transformational leadership and job performance. Data were collected from various private sector organizations in Islamabad and Gilgit regions of Pakistan. A total sample size of 319 was recorded. Structural equation modeling via SmartPLS software was used to test the hypotheses. Results supported our proposed hypotheses. Several theoretical and practical implications are discussed.
Keywords: 330; green transformational leadership; psychological contract fulfillment; jobperformance; social identity theory; social exchange theory; non-green behaviors; Pakistan